Akad Kerjasama Dalam Pengelolaan Kebun Sawit - Absah, Siti; Gunawan, Syafri; Harahap, Risalan Basri (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This research is motivated by the existence of cooperation in the management of oil palm plantations carried out by oil palm farmers in Rambah Hilir District, Rokan Hulu Regency, namely in the form of garden owners giving their planted gardens to plantation workers to be cared for on the basis of trust without direct supervision with money giving fertilizer money in cash. according to the agreement. The main problem in this study is how the cooperation agreement in the management of oil palm plantations in Pasir Utama Village, Rambah Hilir District, Rokan Hulu Regency is reviewed and how is the review of the Sharia Economic Law Compilation regarding the cooperation agreement in the management of oil palm plantations in Pasir Utama Village, Rambah Hilir District, Rokan Hulu Regency. This study uses the field research method (field research) and sourced primary and secondary data. Data collection techniques used in this study were observation, interviews and documentation. The results showed that the cooperation agreement in the management of oil palm plantations was insecure and did not show an element of honesty where the manager did not buy fertilizer money and did not harvest oil palm fruit not only taking the ripe fruit but also taking the unripe oil palm fruit so that the owner of the oil palm feel aggrieved by the manager. Cooperation agreements in the management of oil palm plantations in the community sometimes do not heed the applicable sharia law, so that they can harm one another. This happens because of ignorance of the community in the cooperation agreement.